Thinking Skills and Philosophy for Children: The Bethlehem Program, 1982 - 1983 - Martin, John F.; Weinstein, Mark L. (Analytic Teaching, 2014)
Introduction:  During the past decade, the Philosophy for Children Program has offered teacher-training workshops throughout the United States and elsewhere.  The workshops frequently supported by grants, enable teachers to work with a professional philosopher in developing the skills required for teaching critical thinking to elementary and intermediate schools.